Dipsacus fullonum: an Alternative Host of Sunflower chlorotic mottle virus in Argentina - Giolitti, Fabián; Bejerman, Nicolás; Lenardon, Sergio (Journal of phytopathology, 2009)
Dipsacus fullonum L. is a biennial weed that is widely spread in the Pampean region of Argentina. Plants of this species showing leaf mosaic symptoms were collected near sunflower (Helianthus annuus L.) crops infected with Sunflower chlorotic mottle virus (SuCMoV). Symptomatic plants were tested by biological, serological and molecular assays. Sunflower and Nicotiana occidentalis L. plants mechanically inoculated with extracts from symptomatic D. fullonum leaves developed typical SuCMoV symptoms. Samples were DAS-ELISA positive when probed with a SuCMoV antiserum. RT-PCR was used to amplify the whole coat protein gene of the infecting virus. An 807 bp fragment was amplified, cloned and sequenced. The deduced amino acid sequence (EU606023) shared 96% amino acid identity with the SuCMoV sequence (AF255677). These results indicate that D. fullonum mosaic is caused by an isolate of SuCMoV. Thus, this finding has epidemiological relevance as the weed may act as a natural virus reservoir.